Challenges and Prospect to Islamic Accountants Take on Industrial Revolution 4.0. - Agus Arwani (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2020)
The purpose of this study is to provide an overview of the challenges and expectations of Islamic accountants in the industrial revolution era 4.0. This study uses a literary approach, by examining several references relating to the industrial revolution 4.0 relating to Islamic accountants. Theories in research use theories related to the industrial revolution 4.0 and related theories related to collaborative Islamic accounting including Popkoya et all theory IR and Iwan Triyuwono's theory SA. The results of this paper that the Era of the industrial revolution 4 which offers convenience and speed makes people turn into super-fast. Technology is used and developed to accelerate the achievement of every goal set by humans. In the end, the material and psychological needs become inevitable to be forgotten, it will only increase. Professional accountants and Islamic accountants need a pattern of self-management of the basic functions of Islamic accountants and accountants which certainly increases the efficiency and effectiveness of work and the results are immediately known (real-time). The findings of this study include the challenges of Islamic accounting in the face of the industrial revolution including the provision of information that is financial and non-financial IT-based, accountability of financial statements in accordance with SAK Sharia is the main basis for policy makers, Sharia accountants must understand the development of IT-based economics and be able to harmonize conflicts of interest by following the development of information technology. The expectation of Islamic accountants in facing the industrial revolution can be accepted and has the knowledge and skills of IT-based SAK Sharia and can apply digital-based technology, Islamic Accountants always want to innovate in technology development and Islamic accountants are always adaptive in economic and technological development and always want to learn throughout time